Beam Selection Algorithm for Beamspace HAP-MIMO Systems Based on Statistical CSI - Zou, Shiyi; Jiang, Lingge; Ji, Pingping; He, Chen; He, Di; Zhang, Guorong (2021 International Conference on Networking and Network Applications (NaNA), 2021)
In this letter, a beam selection algorithm is put forward for beamspace high altitude platform massive multiple-input multiple-output (HAP-MIMO) systems. Specifically, the algorithm is subject to the maximization of match degree between the beams and users, which is constructed by exploiting statistical channel state information (CSI). The beam selection is partitioned into two parts. In the first part, we obtain a reduced-dimensional dominant beam set consisting of each user's most preferred beams according to the match degree. In the second part, we formulate the selection of optimal beams from the dominant beam set as an assignment problem that can be solved by Kuhn-Munkres algorithm. Numerical results demonstrate the performance enhancement of the proposed algorithm with respect to energy efficiency.